Assessing the impact of European Integration on sectoral trade in services - Nadine Behncke (FIW - Research Centre International Economics, 2013)
The present paper contributes to the existing literature analyzing the relationship between intra EU trade in services and European Integration by taking into consideration a potential endogeneity bias of the EU dummy and a correct specification of multilateral resistance terms in a panel data set covering the years 2000-2010. Our results offer evidence for a high positive impact of European integration on aggregate services trade between member states while we find a negative effect of monetary integration. However, there exist notable differences at the sector level. According to our results, European integration has positive effects especially for business services, travel and EDV services. Analyzing the evolvement of the sectoral EU-effects over time shows that exports of EDV and OBS have steadily increased due to European integration.
Keywords: F13; F15; 330; Trade in Service; European integration; gravity equation